Karakteristik Penggunaan Plastik PVC (Polyvinyl Chloride) Bahan Tambahan Campuran Aspal Porus - M. Sa'dillah; Yurnalisdel; Blima Oktaviastuti; Calvin Charis Christy Nenabu (Universitas Bengkulu, 2024)
Various types of plastik used by the community, including the plastik used by researchers (Polyvinyl Chloride). This type of PVC is plastik waste made from the polymerization process which is found in everyday life. One of the uses of plastik pellets is as an additional material in making asphalt. Porus which will later function as road construction adhesive. This research aims to (1) Determine the Optimal Asphalt Content value for Marshall properties (KAO) for porous asphalt mixtures (2) Characteristics of the Marshall test to determine the ideal asphalt content by adding PVC plastik waste (3) to determine the effect of adding PVC plastik pellets on performance of porous asphalt. The research method uses experimental research in the laboratory. The research will be carried out using the Australian Asphalt Pavement Association (AAPA) 2004 approach method. Testing for optimum asphalt content (KAO), namely at a level of 5%, meets the Asphalt Pavement Association (AAPA 2004) specifications for porous asphalt mixtures. Mixture testing with variations in PVC plastik content of 4% has met Australian specifications (AAPA 2004) including VIM, VMA, Stability, Flow and MQ testing.